(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article is devoted to tax policy in conditions of macroeconomic instability. Using Russia as a case study, the paper analyses anti |antirecessionary measures and their impact on the economy. The following problems have been identified: uneven support, administrative complexities, and the shadow economy. Paths for improving the tax system are proposed.